JUSTIFICATION OF USING NEURAL NETWORKS TO SOLVE EQUATIONS WITH FRACTIONAL INTEGRALS - Gorskaya, Tatiana; Galimyanov, Anis; Nguyen, Tien (Uzbekistan Open Conference, 2025)
The application of neural networks for solving one integral equation of fractional order is investigated. The application of the least squares method for the numerical solution of the equation is substantiated, a computational scheme using neural networks is constructed, the parameters of which are found by the least squares method, and the convergence of approximate solutions to the exact one is estimated.
Keywords: numerical methods; integral equations; fractional-order equations; approximation of functions; neural networks